Characterization of Type-III Resistant Starch Produced by High Shear Mixing Combined with Membrane Separation - Putu Ayu Yuliani Indiasih; Muhammad Faturahman Almuhaimin; Muh. Abdillah Taufiqurrahman; Bramantyo Airlangga; Sumarno (IPTEK The Journal of Engineering, 2023)
There are five types of resistant starch and the most commonly used as functional food is type-III resistant starch (RS-III), which is a retrograded of gelatinized starch that is conventionally produced by heating and cooling treatment. This study characterized the RS-III produced by an unconventional method by modification of high shear mixing (HSM) combined with membrane microfiltration from cassava starch. A starch/water mixture with a concentration of 1/20 w/v was gelatinized in the HSM reactor at 95°C for 15 minutes and then separated using membrane microfiltration. The separated permeate was cooled to the retrogradation process. The products were characterized by iodine, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Total Dietary Fiber (TDF) content. The highest amylose content that can be achieved was 15.3% with a degree of crystallinity of 8.58%. The higher HSM speed significantly increased the TDF content in RS-III products up to 12.33%.